Potential action of cardamom (Elettaria cardamomum) against triple-negative breast cancer - Akash Samanta; Kiran Dobhal; Alka Singh; Shalu Verma; Vikash Jakhmola (Wolters Kluwer Medknow Publications, 2023)
Triple-negative breast cancer (TNBC) has been known as havoc among females globally. It is a heterogeneous group of cancer encompassing many breast cancers basically distinct by the lack of estrogen receptor, progesterone receptor, and overextension of the human epidermal growth factor receptor-2 gene. It can be caused by various factors, namely unbalanced diet, beverage consumption, smoking, hormonal imbalance, medication, genetic factor, and decreased levels of physical activity. It represents one of the most aggressive types of breast cancer, and researchers revealed that the chemical components of cardamom, namely limonene, cymene, pinene, linalool, borneol, cardamonin, indole-3-carbinol, and diindolylmethane, primarily target the programmed cell death lignin-1 gene of cancer which is more abundant in cancer cells than in healthy cells. There is no standard chemotherapy session for eradicating TNBC because targeted receptor absents in cancer cells as present in common breast cancer. Cardamonin has been identified as an effective component that targets most of the signaling pathways against TNBC. Metallic chelates of cardamonin with copper ion help to improve lipophilicity and bioavailability in cancer cells. The literature included in this review was assessed from the international databases, namely PubMed, Elsevier, Scopus, Google Scholar, Bentham, and Research Gate journals published between 2010 and 2023. Utilizing keywords for literature searching are breast cancer, triple negative breast cancer, cardamom, bioavailability, and cardamonin. A safe and efficient targeted therapy for this cancer has been difficult to develop due to its rapid proliferation and indefinite signaling pathway. Literature investigation enlightened that phytoconstituent reported in the cardamom reporting anticancer potential action against TNBC. Data concluded from this review can prove beneficial to the communal population in the treatment of TNBC and improve the health indicator in the future.